Kontribusi Daya Ledak dan Koordinasi Mata-Tangan terhadap Jump Shoot Atlet Bolabasket Putra - Adelwis Putri Maynarez; Fahd Mukhtarsyaf; Bafirman; Nugroho Susanto; Ridho Bahtra (MAN Insan Cendekia Jambi, 2026)
This study examined the contribution of leg-muscle explosive power and hand-eye coordination to the jump-shoot performance of male basketball athletes in Padang City. A quantitative correlational design involved 30 athletes aged 16-17 years from Starone, Andromeda, and Atlantis clubs, selected through purposive sampling. Explosive power was measured using a vertical jump test, hand-eye coordination using a wall-toss test, and jump-shoot performance using a medium-range shooting test from five positions. Data were analyzed through descriptive statistics, the Liliefors normality test, Pearson correlation, t tests, and multiple correlation and the F test at a 0.05 significance level. The results demonstrated a positive and significant relationship between explosive power and jump-shoot performance (r=0.485; t=2.935), and between hand-eye coordination and jump-shoot performance (r=0.426; t=2.492). Simultaneously, both predictors produced a multiple correlation coefficient of R=0.565, F=6.330, and explained 31.92% of the performance variance. These findings indicate that jump-shoot development should integrate lower-limb explosive training with structured visual-motor coordination exercises.